Optimasi Kepuasan Pelanggan Melalui Teknologi Informasi dan Komunikasi Omnichannel Beko Appliances Indonesia - Angga Aulia Jaya; Fajarina Fajarina (Universitas Prof. Dr. Moestopo (Beragama), 2026)
This study aims to examine how the implementation of an omnichannel-based information and communication technology system optimizes customer satisfaction at PT Beko Appliances Indonesia and to identify the challenges that emerge during its implementation. The novelty of this research lies in the integration of Media Richness Theory and CRM concepts in analyzing omnichannel service systems, making it one of the first in-depth case studies to explore omnichannel implementation within the home-appliance industry. Using a post-positivist paradigm and an interpretive qualitative case-study design, data were collected through in-depth interviews with key informants, observations of the company’s omnichannel system, and supporting literature review. The findings indicate that the omnichannel system significantly enhances customer experience, as reflected in the increase in Net Promoter Score (NPS), improved operational efficiency and effectiveness based on rising KPI values, strengthened customer loyalty shown by the Consumer Retention Rate (CRR), and higher product sales. Nevertheless, several challenges persist, including high dependence on internet connectivity, limited system scalability during high-volume interactions, user adaptation barriers, the need for continuous system maintenance, and data security risks. These findings imply that the success of an omnichannel system relies heavily on robust technological infrastructure, comprehensive staff training, and consistent organizational readiness.